Depth-age model based on Lead-210 chronology of short sediment core from Lake 850, Sweden - Petra Zahajská; Carolina Olid; Daniel J Conley (PANGAEA, 2021)
Concentrations of lead 210 (210Pb) were used for dating of a short sediment core, which was taken in March 2019 from ice-covered lake. The core 210Pb concentrations were analyzed using ORTEC high-prurity germanium detector at Lund university and R package Plum was used to build the age-depth model.
In: Zahajská, Petra; Olid, Carolina; Shemesh, Aldo; Conley, Daniel J (2021): Discharges, radon fluxes, dissolved silicon, biogenic silica, stable silicon isotopes of water and sediment samples and XRF data from Lake 850, Northern Sweden [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.929941